A Comprehensive Cost Variation Analysis of Drugs Used in the Management of Type-2 Diabetes Mellitus Across India - Abinish D.G (Journal of Pharmacoeconomics and Pharmaceutical Management)
Background: This study aims to examine the cost variations of oral antidiabetic agents in India, highlighting the financial barriers that may impact patient adherence and treatment efficacy.